Glanzmann’s Thrombasthenia: Role of Angioembolization and factor VII in recurrent bleeding from ulcerated duodenum - Abbas, Ali; Sayani, Raza; Syed Muhammad Mustahsan; Saeed, Anwar (International Journal of Endorsing Health Science Research, 2016)
Introduction: Glanzmann’s thrombasthenia (GT) is a rare, genetically inherited, functional disorder of platelets. The pathology is deficient or dysfunctional platelet glycoprotein IIb/IIIa (GP IIb/IIIa) complex resulting in bleeding diathesis. Case Report: Here in, we report the effectivity of angioembolization with factor VII in a patient with Glanzmann’s thrombasthenia (GT), who presented with recurrent bleeding from duodenal ulcer. Conclusion: Angioembolization with added infusion of factor VII, can be considered an equally effective alternate to platelet transfusion in patients of GT, who present with recurrent bleeding.